PENGARUH PENAMBAHAN ARANG SERBUK KAYU GERGAJI TERHADAP KUAT TEKAN MORTAR - Manullang, Hotmalina; Supriani, Fepy; Gunawan, Agustin (Inersia: Jurnal Teknik Sipil, 2019)
Mortar is a mixture of adhesive (Portland cement and limestone), sand, and water with a certain composition. Mortar is used in structural and nonstructural constructions. This research uses sawdust charcoal as cement addition because in similar research mention that wood charcoal contains silica. This research was aimed to know the value of compressive strength of the mortar (1:3 and 1:5) by using sawdust charcoal as cement addition. The method of manufacture and testing compressive strength of mortar refers to SNI 03-6825-2002. The mortar specimens is cube shaped with side 50 mm and the total of specimens have 112 mortar test specimens. Variations of sawdust charcoal used were 2,5%, 5%, 7,5%, 10%, 12,5% and 15% of the weight of cement. The range of initial flow values used are 105% - 115 (SNI 03-6882-2002). The specimens were soaked for 26 days and compressive strength test of mortar was performed at 28 days. The test results showed that the compressive strength value of normal mortar (1:3) of 25,09 MPa, the value of compressive strength of variation mortar 2,5%, 5%, 7,5%, 10%, 12,5% and 15% respectively are 25,89 MPa, 26,93 MPa, 27,84 MPa, 25,58 MPa, 20,68 MPa and 17,24 MPa. The value of compressive strength of normal mortar (1:5) of 15,48 MPa, the value of compressive strength of mortar variation 2,5%, 5%, 7,5%, 10%, 12,5% and 15% respectively are 15,83 MPa, 16,24 MPa, 17,01 MPa, 15,59 MPa, 14,45 MPa dan 12,26 MPa. The highest increase of compressive strength value in mixture 1:3 was variation 7,5% by 10,94% and mixture 1:5 was variation 7,5% by 9,90% from the compressive strength value of normal mortar.